Conservatism and diversification of plant functional traits: Evolutionary rates versus phylogenetic signal - Ackerly, David (National Academy of Sciences, 2009)
The concepts of niche conservatism and adaptive radiation have played central roles in the study of evolution and ecological diversification. With respect to phenotypic evolution, the two processes may be seen as opposite ends of a spectrum; however, there is no straightforward method for the comparative analysis of trait evolution that will identify these contrasting scenarios. Analysis of the rate of phenotypic evolution plays an important role in this context and merits increased attention. In this article, independent contrasts are used to estimate rates of evolution for continuous traits under a Brownian motion model of evolution. A unit for the rate of phenotypic diversification is introduced: the felsen, in honor of J. Felsenstein, is defined as an increase of one unit per million years in the variance among sister taxa of ln-transformed trait values. The use of a standardized unit of measurement facilitates comparisons among clades and traits. Rates of diversification of three functional traits (plant height, leaf size, and seed size) were estimated for four to six woody plant clades (Acer, Aesculus, Ceanothus, Arbutoideae, Hawaiian lobeliads, and the silversword alliance) for which calibrated phylogenies were available. For height and leaf size, rates were two to ≈300 times greater in the Hawaiian silversword alliance than in the other clades considered. These results highlight the value of direct estimates of rates of trait evolution for comparative analysis of adaptive radiation, niche conservatism, and trait diversification.